RIFM fragrance ingredient safety assessment, 2-octenoic acid, 4-ethyl-, (2E)-, CAS Registry Number 60308-76-1. (March 2023) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Cancellieri, M.A.; Chon, H.; Dagli, M.L.; Dekant, W.; Deodhar, C.; Fryer, A.D.; Jones, L.; et al.
Highlights: 2-Octenoic acid, 4-ethyl-, (2E)-; a safety assessment based on RIFM's criteria. A safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.